Valproic acid Population Pharmacokinetics in Asian Pediatric Epileptics: A Systematic Review - Hidayat, Muh. Faris; Purwantiningsih, Purwantiningsih; Pinzon, Rizaldy Taslim (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
The pharmacokinetic profile of valproic acid in pediatric subjects in Asian populations is lacking. One of the most useful ways to develop a personalized dosing strategy is to use population pharmacokinetics. The focus of this systematic review is to describe the population pharmacokinetic profile of valproic acid (VPA) and determine the variables influencing pharmacokinetic models of the drug in children with epilepsy that have been published in Asian journals. A comprehensive literature search was carried out from 2014 to 2024 on Science Direct and PubMed. Keywords used valproic acid, valproic, VPA, sodium valproate and population pharmacokinetic, pharmacokinetic model. In this review, four studies were considered. The pharmacokinetic model was developed by looking at several covariates that significantly affect the population pharmacokinetics of VPA using TDM data from pediatric epilepsy patients. The clearance value and volume of distribution of VPA can be seen to be in the range of 0.148 - 3.19 L/h, and 0.317 - 24 L/KgBB. In addition, subjects with SCN1A A/A genotype showed a decreased therapeutic effect of VPA. Significant covariates affecting the pharmacokinetics of VPA were age, dose, and the use of comedication with other anti-seizure drugs.